Oral Chronic Graft-Versus-Host Disease - Dean, David; Sroussi, Herve (Frontiers in Oral Health, 2022)
Chronic oral graft-versus-host disease (cGVHD) is a complex, frequent, and highly impactful complication of allogeneic hematopoietic cell transplantation (alloHCT). It represents the leading cause of morbidity and mortality in long-term alloHCT survivors. cGVHD can affect almost any visceral organ system and commonly affects the skin, eyes and mouth, manifesting with signs and symptoms similar to other known immune-mediated and autoimmune diseases. Oral manifestations of GVHD include inflammation, thinning, and ulceration of oral mucosal tissues (similar to lichen planus), lymphocyte-mediated salivary gland dysfunction (similar to Sjögren/Sicca Syndrome), and decreased oral opening (trismus) secondary to sclerosis of oral and perioral tissues (analogous to what is observed in scleroderma). Oral cGVHD can results in severe mucosal pain, compromised nutrition, weight loss, limitation in opening, and sometimes irreversible fibrosis of the salivary glands. While some cases can be managed with topical therapies, management may also require long-term targeted immunosuppressive and/or corticosteroid therapy with associated risk of local and systemic infection, hyperglycemia, kidney dysfunction, osteopenia/osteoporosis, and possibly secondary malignancies. The aim of this mini-review is to provide an up-to-date review of literature related to the diagnosis and management of oral cGVHD to aid dental and medical clinicians in optimizing oral cGVHD therapy while minimizing potential adverse effects.